Parental disciplinary practices and internet addiction in adolescents - Araújo Rodrigues, Daisy (2022)
This study aimed to explore the relationship between parental disciplinary practices and internet addiction. 568 adolescents participated. A Sociodemographic Questionnaire, the Internet Addiction Test (IAT) and the Dimensions of Discipline Inventory - Form C (DDI-C) were used. 73.1% of users with mild and moderate addiction were identified. Mothers showed greater use of all disciplinary dimensions. Differences were found only in the father's inductive discipline, depending on the family setting. However, there were no differences between adolescents from different family setting regarding internet addiction. Associations were observed between parental disciplinary dimensions and internet addiction. Finally, the punitive discipline of the mother and father and the inductive discipline of the mother, were predictors of internet addiction.